An Assessment of the Communication Management System (CMS) of Midway Colleges - Ervhin Bryan de Luna (Humanities, Society, and Community, 2023)
Since society shapes the century we live in, effective communication plays a crucial part in developing our community. It is considered a fundamental and empowering process that efficiently transforms people to be participative, especially in an educational setting. In a place where learning occurs, ensuring the appropriate administration and delivery of processes, procedures, instructions, and other relevant information is essential. This research study aims to present a narrative of the general analysis of Midway Colleges, Inc.'s communication management system (CMS) assessment. In order to achieve its primary objective, assessments were drawn to the information environment, rules, and cycle of communication assessments of the school. The data was treated quantitatively. Three hundred fifty-two internal and external stakeholders of the school participated in answering the study survey questionnaire, which was randomly selected. From the disclosed data collection results, respondents agreed on how the school manages its communication system in terms of the quality of information, communication flow structure, and media and communication platforms. The stakeholders provided some recommendations for maintaining improved communication management systems, such as (1) establishing a standard communication system for Midway Colleges, Inc.; (2) developing organizational list handling communication processes; and (3) provisioning training or seminars for internal stakeholders responsible for information dissemination.